Signaling pathway in breast cancer therapy - Niloofar Mansouri; Melika Daneshgar; Farzaneh Khojasteh; zahra Modaresi; Reza Taheri; Parisa Mokabberi; Mohammad-Reza Saberi; Jamshidkhan Chamani (Avicenna Journal of Phytomedicine)
Objective: This research attempted to increase the bioactivity and solubility and reduce the side effects of Tamoxifen (TMX) by using the cellulose nanocrystals (CNCs) extracted from walnut shells as a carrier and studied the interaction behavior of CNCs-TMX with hemoglobin.Materials and Methods: The synthesized CNCs and CNCs-TMX were analyzed through the usage of XRD, FTIR, TEM, SEM, and multi-spectroscopic techniques. A real-time PCR assay was also conducted to further unravel the underlying mechanism of CNCs-TMX.Results: Our synthesized products including CNCs and CNCs-TMX had spherical morphologies in small sizes of 17.42 nm and 56.38 nm, respectively. The changes in FTIR spectrum signified the induced alterations in the samples functional group during the steps of preparation, while the crystallinity index of CNCs was 71.35%. Fluorescence spectroscopy confirmed the quencher functionality of CNCs-TMX along with the dominance of static quenching mechanism. Also, synchronous fluorescence displayed its binding to Hb in the vicinity of Tryptophanresidue. FRET was applied to calculate the interaction energy transfer of 0.18 nm. Next to achieving satisfactory results from oxygen-hemoglobin dissociation studies, the presence of CNCs-TMX caused a reduction in hemoglobin affinity for oxygen.Conclusion: Our findings pointed out the remarkable potential of TMX-loaded CNCs, derived from walnut shell, in suppressing the proliferation, migration, and invasion of breast cancer cells by quelling the RAS/RAF/MEK/MAPK signaling pathways. The gathered data approved the promising applicability of the obtained CNCs from walnut shell in the delivery system of anti-cancer drugs throughout pharmaceutical applications.